Kemampuan Siswa Kelas X SMA Negeri 2 Banda Aceh Menganalisis Isi Debat - Edo Syafriky; Saifuddin Mahmud; Sa’adiah Sa’adiah (JIM Pendididikan Bahasa dan Sastra Indonesia, 2019)
This study examines the ability of class X students of SMA Negeri 2 Banda Aceh to analyze the content of the debate. The formulation of the problem is (1) How is the ability of class X students of SMA Negeri 2 Banda Aceh to analyze problems / issues in the debate text? (2) How is the ability of class X students of SMA Negeri 2 Banda Aceh to analyze the perspective of the arguments of several parties in the debate text? (3) How is the ability of class X students of SMA Negeri 2 Banda Aceh to analyze the conclusions in the debate text? The purpose of this study (1) Describe the ability of class X students of SMA Negeri 2 Banda Aceh to analyze problems / issues in the debate text. (2) Describe the ability of class X students of SMA Negeri 2 Banda Aceh to analyze the point of view of the arguments of several parties in the debate text. (3) Describe the ability of class X students of SMA Negeri 2 Banda Aceh to analyze the conclusions in the debate text. This research uses descriptive quantitative research methods. The population of the study was 27th grade students of SMA 2 Banda Aceh, totaling 279 students. Meanwhile, the study sample was 42 students. The research data collection technique is a non-test technique in assignment. Data analysis was carried out from the results of analyzing the problem / issue, the perspective of the arguments of several parties and the conclusions in the debate text. The result of the average value of analyzing the problem / issue is 60. The result of the average value of analyzing the point of view of the arguments of some parties is 82 and the result of the average value analyzing the conclusions is 48. The result of the overall average value is 61. The results of this study indicate that the scores obtained by students in the range of the good (86-100) were 7 (17%) students, in the good category (71-85) as many as 5 (12%) students, in the sufficient category (56-70) as many as 15 (36%) students, and less categories with grades 40-55 as many as 15 (35%) people. Thus, the ability of class X students of SMA Negeri 2 Banda Aceh to analyze the content of the debate can be categorized as sufficient.